Konflik Pengawas Dengan Kepala Sekolah Dalam Pelaksanaan Supervisi Manajerial Di Kota Pekanbaru - Said Suhil Achmad (Jurnal Pendidikan, 2012)
Principals in performing their duties will receive supervision from supervisors,particularly in the managerial aspects, but its implementation is expected to be conflict, because noteveryone is able to work with a bunch of good, especially the organizational structure in which certainpeople are worth it or not placed there it would trigger conflict, high conflict How did that happen?How high intensity. This is the assessment in this study, namely to determine the level of conflictbetween the principal and superintendent with the level of intensity due to the conflict between thesuperintendent to the principal; relationship between the level of conflict with supervisors conflict; withthe principal, and superintendent for the differences in the level of conflict the principal factors gender,education level, and years of supervisor. This study classified descriptive study, carried out inaccordance with the stage of the research is to test instruments, data collection, and data analysis. Datacollection using the questionnaire in the form of a Likert scale, while data analysis is done using themethod with the help of SPSS Statistics version 17. The population of this research is all the schoolsuperintendent in the city of Pekanbaru as many as 96 people. Sampling using "proportionate stratifiedsampling", the stage of confidence of 5%, ie 74 people, most of the respondents used to testinstruments. Penyeberan questionnaires for the test conducted by the coordinator supervisor, namelythe 30 respondents. questionnaire of 52 items, 6 items declared them invalid and reabel. Data collectionwas conducted to 63 respondents, but only 85% were worthy of the sample, it can be said to be eligiblefor analysis. In accordance with the method of research used the hypothesis analyzed with descriptiveand inferential statistics. The result is the level of conflict by 54% or half of the maximum score, or inthe medium category, and the intensity of the conflict between the superintendent to the principal witha score of 90% of the maximum score. Hypothesis test results indicate that there is a positive andsignificant relationship between the level of conflict and the intensity of the conflict with 0.587correlation coefficient and the coefficient of determination (r2) 34%. Mean variance occurs in thevariable intensity of the conflict by 34% can be explained by the variance that occurs in variable levelsof conflict and 66% specified other factors. There is no difference in the level of conflict by gender,level of education and years of supervisor.